2018
DOI: 10.1111/aos.13889
|View full text |Cite
|
Sign up to set email alerts
|

The penetration and distribution of topical atropine in animal ocular tissues

Abstract: Purpose: To conduct a multi-tissue investigation on the penetration and distribution of topical atropine in myopia treatment, and determine if atropine is detectable in the untreated contralateral eye after uniocular instillation. Methods: Nine mature New Zealand white rabbits were evenly divided into three groups. Each group was killed at 5, 24 and 72 hr, respectively, following uniocular instillation of 0.05 ml of 1% atropine. Tissues were sampled after enucleation: conjunctiva, sclera, cornea, iris, ciliary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 60 publications
(88 reference statements)
1
20
1
Order By: Relevance
“…In the human body, atropine metabolism produces small (3%) amounts of tropic acid [ 58 ] and atropine is mostly excreted unchanged in the urines. During ophthalmic administrations in rabbits, it has been shown that atropine has good ocular bioavailability via both transcorneal and transconjunctival-scleral routes [ 59 ]. Unfortunately and to the best of our knowledge, atropine metabolism in the eye has not been studied despite there being a clear incentive to do so, like for other drugs [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the human body, atropine metabolism produces small (3%) amounts of tropic acid [ 58 ] and atropine is mostly excreted unchanged in the urines. During ophthalmic administrations in rabbits, it has been shown that atropine has good ocular bioavailability via both transcorneal and transconjunctival-scleral routes [ 59 ]. Unfortunately and to the best of our knowledge, atropine metabolism in the eye has not been studied despite there being a clear incentive to do so, like for other drugs [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the drug concentration ranges observed for the dorsal and ventral cornea (1.03-9.45 μg/g), if protein binding is similar to serum, voriconazole is expected to be above the target MIC for up to 48 h, which is of significance for the treatment of keratomycosis [35,36]. The maintenance of voriconazole concentrations in ranges from 1.04-14.22 μg/g in the sclera is of importance, since transcleral drug diffusion is very efficient in allowing drug molecules to reach the cornea [37]. Our data showed significant individual variation in voriconazole concentrations, both in tissues as in tears, therefore, in some individuals, therapeutic concentrations might not be reached in tissues other than the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…In the rabbit, topical atropine reaches the vitreous and also retina, 32 so it is possible that some of the effects of atropine we observed arose from scleral or retinal effects. It is possible that the atropinized eyes became amblyopic.…”
Section: Effect Of Atropine On Refractive Error and Vitreous Chamber mentioning
confidence: 96%